2020
DOI: 10.1016/j.ridd.2019.103551
|View full text |Cite
|
Sign up to set email alerts
|

Persistent handwriting problems are hard to predict: A longitudinal study of the development of handwriting in primary school

Abstract: General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights. • Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…In this respect, unsatisfactory is a more neutral term, and is meant to indicate current handwriting quality relative to an age-specific norm. In previous work we showed that unsatisfactory handwriting at a younger age does not necessarily result in handwriting problems at an older age (Duiser et al, 2020). Second, in DSM-IV dysgraphic, handwriting is no longer presented (Biotteau et al, 2019).…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…In this respect, unsatisfactory is a more neutral term, and is meant to indicate current handwriting quality relative to an age-specific norm. In previous work we showed that unsatisfactory handwriting at a younger age does not necessarily result in handwriting problems at an older age (Duiser et al, 2020). Second, in DSM-IV dysgraphic, handwriting is no longer presented (Biotteau et al, 2019).…”
Section: Discussionmentioning
confidence: 84%
“…Finally, it must also be pointed out that we distinguished satisfactory and unsatisfactory handwriting in children that are still at learning stage, but do not necessarily have satisfactory and unsatisfactory developmental outcomes (Duiser et al, 2020). This may reduce generalizability of the findings.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 89%
See 2 more Smart Citations
“…Grade 2 and Grade 4 students were chosen for several reasons. Adequate proficiency can only be expected with enough practice (Duiser et al, 2020), with handwriting stability expected within the second half of Grade 3 (Overvelde & Hulstijn, 2011). Furthermore, in Bavaria, teachers accompany their classes for 2 years: Grades 1 to 2 and then Grades 3 to 4.…”
Section: Participantsmentioning
confidence: 99%